From endangered to preserved: Biobanking of the Katchaikatti Black sheep through dermal fibroblast cryopreservation - G. Nagarajan,; Rajiv Kumar,; G. S. Yadav,; Rekha Sharma,; Arun Kumar, (Journal of Livestock Biodiversity, 2025)
The present study was carried out with the aim of ex-situ conservation of the elite germplasm of Indian sheepbreeds including Katchaikatti Black sheep in the form of cryo cell bank repository. The Katchaikatti Black sheepare distributed in the villages of Vadipatti block of Madurai district in Southern Tamil Nadu and belong to themeat type sheep with extremely coarse and hairy wool. As on date, Katchaikatti black sheep breed is at the riskof extinction and considered to be endangered. It is therefore imperative to conserve the highly valuable sheepgermplasm of Indian origin. In this connection, as a preliminary step, a total number of eight ear pinna sampleswere collected from eight individual sheep (four males and four females from Katchaikatti village) using the sterilesurgical blade, washed once in 70 % alcohol, saturated once in washing medium, stored in complete cell culturemedium and transported under cold chain. Once in six hours, the complete medium was changed. After bringingto the laboratory at ICAR-CSWRI, Avikanagar, standard cell culture protocol was followed for the initial tissueexplant culture. Subculturing of the resultant somatic fibroblast cell was done up to the passage four level at theperiodical intervals. In order to use the skin fibroblasts in downstream processing, karyotyping was also carriedout through outsourcing, as a gold standard. Various parameters such as viability assay, population doublingtime were also carried out. As a final step, cryopreservation of the skin fibroblast cells derived from Katchaikattiblack sheep was done using LN2 protocol, after the completion of the standard characterization regimen.